Dietary Niacin Supplementation Suppressed Hepatic Lipid Accumulation in Rabbits - Lei Liu; Chunyan Li; Chunyan Fu; Fuchang Li (Asian-Australasian Journal of Animal Sciences, 2016)
An experiment was conducted to investigate the effect of niacin supplementation on hepatic lipid metabolism in rabbits. Rex Rabbits (90 d, n = 32) were allocated to two equal treatment groups: Fed basal diet (control) or fed basal diet with additional 200 mg/kg niacin supplementation (niacin). The results show that niacin significantly increased the levels of plasma adiponectin, hepatic apoprotein B and hepatic leptin receptors mRNA (p<0.05), but significantly decreased the hepatic fatty acid synthase activity and adiponectin receptor 2, insulin receptor and acetyl-CoA carboxylase mRNA levels (p<0.05). Plasma insulin had a decreasing tendency in the niacin treatment group compared with control (p = 0.067). Plasma very low density lipoproteins, leptin levels and the hepatic adiponectin receptor 1 and carnitine palmitoyl transferase 1 genes expression were not significantly altered with niacin addition to the diet (p>0.05). However, niacin treatment significantly inhibited the hepatocytes lipid accumulation compared with the control group (p<0.05). In conclusion, niacin treatment can decrease hepatic fatty acids synthesis, but does not alter fatty acids oxidation and triacylglycerol export. And this whole process attenuates lipid accumulation in liver. Besides, the hormones of insulin, leptin and adiponectin are associated with the regulation of niacin in hepatic lipid metabolism in rabbits.